Peningkatan Kesadaran Hukum Mengenai Perlindungan Anak Bagi Siswa dan Guru di SMP Negeri 2 Luwuk - Dian Ekawaty Ismail; Avelia Rahmah Y. Mantali; Mohamad Rivaldi Moha; Dolot Alhasni Bakung; Usman Rasyid (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Children as the next generation of the nation, must be protected from childhood to adulthood. If a child has been in an environment of crime since childhood, that child can become a criminal in the future, and will disturb people's lives. It is wise for child protection to start in junior high school. Junior high school (SMP) as a place for children to gain knowledge, begins to learn to get along with peers, smaller friends or teachers and begins to understand ways to commit violence against others. Therefore, the protection of children and teachers is currently an important matter and must be a common concern. Lack of understanding and knowledge of legal protection for children in the school environment has resulted in many violations and even criminal acts of violence against children in the school environment. As a result, children do not feel comfortable at school, skip school, or even drop out. Taking into account the legal issues above, the law faculty community service team carried out this service activity as an effort to increase public awareness and teachers that the importance of child protection starts from a child-friendly school environment and teachers. Regarding these problems, we all must pay attention to the protection of children and teachers, including at SMP Negeri 2 Luwuk. In this community service, we provide counseling and outreach to the concept of child protection, namely the urgency of legal protection for children and teachers in schools. The outputs that will be produced through this service are legal counseling activities for the community, scientific articles in the Community Service Journal, Publication in the Media Period (Print/Online), then Mandatory Reports in the form of Service Implementation Results Reports, Activity Diary Books and Financial Record Books.